Can the intensity of menopausal symptoms be modified? The pilot study of the effects of an intervention programme designed for 48-54-year-old women - Ambroziak, Ewa; Bielawska-Batorowicz, Eleonora (Menopause Review/Przegląd Menopauzalny, 2011)
Objectives: Psychological interventions are effective ways to modify experience of menopause. They provide evidence-based data on menopausal transition and develop skills for symptoms’ management. The designed intervention programme included information on hormonal mechanisms, symptoms and the impact of menopause on health, and offered exercises aimed at recognition of bodily sensations and their control. A study was conducted to evaluate its effects. Design : Cross-sectional, with two-week follow-up. Material and methods: Women aged 48-54 yrs were recruited at meetings of non-governmental organizations and divided into 2 groups (study, n = 30 and control, n = 30). Participants filled in (time 1): demographic questionnaire, Menopause Symptoms List (MSL), Type D Personality Questionnaire (DS-14), Menopause Representation Questionnaire (MRQ). At time 2 (2 weeks after the intervention) all women filled in MSL and MRQ. The study group evaluated the intervention immediately after it and 2 weeks later. Results : The study group reported a significant (p < 0.001) decrease in intensity and frequency of vasomotor and psychological symptoms, and a decrease in intensity of somatic symptoms; more positive attitudes towards menopause (p < 0.001) were expressed. In both groups, a significant correlation was found for frequency and intensity of all types of symptoms and DS-14 scores (p < 0.001). Positive opinions on the workshop increased with the time. Conclusions: The findings indicate the potential to change experiences by the designed psychological intervention. A relatively short follow-up requires cautious interpretation of the effects of the programme.